(untitled) (Sains Humanika, 2008)
This paper comments on the issue of quality management system implementation in an organization. General explanation on ISO 9000 is given to provide basic understanding on the subject. Analysis of the focus of studies in previous research was done to initiate the discussion. The following discussions and comments are focused on the issue of ISO 9000 implementation, certification motives and its impact on the performance of an organization. The discussions and comments are based on previous empirical findings. Finally, the lesson that can be learned from previous empirical research is that in order to gain positive impact in the long run, ISO 9000 should be implemented for quality improvement.